Antibiotic stewardship: Konzeption und Umsetzung in der stationären Kinder- und Jugendmedizin - Hübner, Johannes; von Both, U; Tenenbaum, Tobias; Weichert, Stefan; Liese, J.; Hufnagel, M.; Pecar, A.; Strenger, V.; Simon, A. (Monatsschrift Kinderheilkunde, 2019)
Background: The worldwide increase in antibiotic resistance has resulted in a focus on a rational and critical use of antibiotics in all areas of medicine. A wealth of structural measures has been developed, particularly for inpatient treatment, which are referred to as antibiotic stewardship (ABS) although only few summaries and guidelines are available for children.ObjectivesIn the interdisciplinary guidelines summarized here, a team of authors has reviewed the published literature in the field of pediatrics and, on the basis of these publications, has drawn up recommendations and reached a consensus with specialist societies involved in antibiotic treatment of children. The guidelines are intended to ensure a rational, restrictive and guideline-compliant use of antibiotics in inpatients in pediatric hospitals, as well as the sensible use of microbiological diagnostics. In the long term these guidelines should improve the quality of antibiotic prescriptions in inpatient treatment of children and adolescents, protecting patients from the undesired effects of inadequate antibiotic therapy and reducing the risk of selection of bacterial pathogens with special resistances and multi-drug resistance.Material and methodsThe guidelines were developed by the working group Antibiotic Stewardship of the DGPI by an editorial committee consisting of J. Hübner, A. Simon, T. Tenenbaum, J. Liese, M. Hufnagel, S. Weichert, U. von Both, A. Pecar and V. Strenger and consented by mandated representatives of other professional associations (ADKA, DAKJ, DGHM, DGKJ, DGI, GNPI, GPOH, GPGE, GPP, ÖGKJ, PIGS, PEG, BVKJ, DGKH, DGKCH) in an internet-based Delphi procedure. The working group Antibiotic Stewardship of the DGPI compiled a thematically structured bibliography after a literature search via Medline/PubMed including the bibliographies of current reviews and meta-analyses. Keywords were “antibiotic stewardship”, “antimicrobial stewardship”, “pediatrics”, “pediatric antimicrobial stewardship”, “stewardship” and “antimicrobial resistance”. Conflicts of interest were disclosed in accordance with the AWMF regulations.ResultsA total of 70 recommendations on structural conditions, antimicrobial therapy, diagnostic aspects (microbiology, resistance testing), further education and training, quality indicators and clinical infectiology audits, role of information technology, nosocomial infections, significance of Clostridium difficile in pediatric patients, management of multi-drug resistant pathogens and the pediatric specialties neonatology and pediatric oncology were developed.ConclusionThe guidelines presented here represent the first such guidelines for the field of pediatrics in the German-speaking area and will be helpful in establishing and evaluating ABS programs in pediatrics and pediatric oncology.
Gesehen am 13.12.2019